Overextension of Nonsetting Calcium Hydroxide in Endodontic Treatment: Literature Review and Case Report - Shahravan, Arash; Jalali, Shahrzad; Mozaffari, Behrooz; Pourdamghan, Nasim (Iranian Endodontic Journal, 2012)
Premixed non-setting calcium hydroxide (CaOH2) paste in pressure syringe system is commonly used in root canal therapy. The aim of this paper is to present a case involving an iatrogenic extrusion of the medicament during endodontic treatment and a literature review of similar reports. The present case demonstrates severe tissue necrosis and other deleterious effects following the extrusion of CaOH2 paste beyond root apex. A 21-year old female was referred for endodontic treatment of her maxillary left first premolar. After completion of the canal preparation, root canals were filled by premixed CaOH2 paste. In the second appointment, a gingival detachment and an irregular zone of necrosis adjacent to the tooth apex was observed. To treat this complication, a mucoperiosteal flap was raised and the extruded material and necrotic tissues were currettaged and the area sutured. The patient was prescribed antibiotics and followed up at 2 weeks, 6 months and 2 years. Two week follow up showed good soft tissue healing. Two years postoperatively, complete radiographic and clinical healing was observed. We can conclude that the application of CaOH2 should be carried out with care and preferably applied free hand or with a lentulo spiral rather than in a pressure syringe.